(3GdfSHI GdMcejIs - (3GdGScOGQj (B, (3GdMfaj, bUjQj RGOg, eMeO Cejf Hf eMeO, J (B1151 (3g`s ((3SjO Hf eMeO Hf SjO eUWais)
(3ChdgG (B:s
(3GdMeO dhdjI hGdUdGI Ydi fHjg agPg QSGdI aj HjGf GdfSHI GdMcejI hZjQgG ef CLRGA GdbVjI GdMedjI hGdTQWjI Ydi QCj GdeJbOejf hGdeJCNQjf Ydi eG Cageg ef ETGQGJ GdYdeGA (B...s
(3BNQgG (B:s
... (3hgPg CjVG Ef bhHd GdMcje jSei SaSWI hEf bhHd HgG GdLOdqj jSei eTGZHI aGdeZGdWI efUQI aj GdbSejf GdSaSWI hGdeTGZHI hGdYeOI Cj GdeYJeO Ydjg GdHQgGf dG ZjQ dCf JMUjd GdYbGFO GdMbI (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\146s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs